PENERAPAN MODEL PEMBELAJARAN MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR MACTH SISWA KELAS IV SDN 011 TANJUNG MEDAN KECAMATAN PUJUD KABUPATEN ROKAN HILIR - Reno Pasla; Otang Kurniaman; Damanhuri Daud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract, The problem this research is the students achievement of macth studies of state elementary school 011 Tanjung Medan fourth graders still low with an average value of 60 and minimum completeness criteria (KKM) sains studies is 70. Between students, amounting to 20 people only 10%, this research is Classroom Action Research (CAR), which aims to improve the student achievement of macth studies class IV at of state elementary school 011 Tanjung Medan with implementation incuiri. Formulation of the problem : is the implementation incuirios macth students can improve students achievement of social studies at of state elementary school 011 Tanjung Medan. The research was conducted on Maret 03, 2015 to April 07, 2014 by 2 cycles. Subjects were students of of state elementary school 011 Tanjung Medan, totaling 20 people who use the data source. The data collection instruments in this thesis is a teacher and students activities sheets an students achievement. This thesis presents the results obtained each day before the action an improve in base score cycle with the average being 60. In the first cycle improve an average of 63,25 and an improve in the second with an average of 75,50. Activities of the teacher in the learning process in cycle of 66,66%, with increase big as 76,16% and the second meeting improve 87,50% and the second meeting improve 100%. Results of data analysis of students activities in the fisrt cycle with the fisrt meeting of an average of 45,80% and a second meeting improve to 62,50% and a second meeting improve to 83,30% at the first meeting of the second cycle with an average of 95,80%. However students achievement also increased the basic score of daily examonatoion as 50% which 10 students passed and 10 students failed. The ending of daily examonatoion as 90% which 18 students passed and 2 students failed. The Impemeltation of cooperative learning make a match type, Resuts in the class III of state elementary school 011 Tanjung Medan that the implementation of incuiri of macth students can improve student achievement of sains studies at fourth graders of state elementary school 011 Tanjung Medan.Key Words : Model cooferative Learning make a match of macth students, fourth graders students Achievement